Small Finger Flexor Tendon Rerupture Occurred 4 Months after Tendon Graft Surgery: A Case Report - Kusakawa, Yuya (International Journal of Orthopedics and Rehabilitation, 2021)
Case report: A right-handed man in his 60s sustained a subcutaneous rupture of the flexor tendon of the left small finger while playing golf. At one month after the injury, a bridge tendon graft was performed using the ipsilateral palmaris longus tendon. A dorsal extension block splint was fabricated the day after surgery, and early mobilization programs were initiated. Referring to previous reports, active finger flexion and extension exercises were performed under wearing the splint until 4-6 postoperative weeks, and full power grip was not allowed until 12 postoperative weeks. However, at 16 postoperative weeks, the moment he swung a golf club, the tendon rerupture occurred. Discussion: No studies have been reported on rerupture after 12 postoperative weeks. The author considered three factors of tendon rerupture. Firstly, it is weakening of the tendon due to steroid injection. Secondly, it is delayed tendon healing due to blood flow disturbance caused by synovial hyperplasia. Thirdly, it is the stress on the small finger flexor tendon of swinging a golf club. Conclusion: Therapists need to plan rehabilitation programs based on analysis of not only past reports but the patients’ background and lifestyle.